Keluhuran Martabat Manusia sebagai Imago Dei : Pandangan Teologi Gereja Katolik - Antonius P Sipahutar; Alexius Poto Obe; Alexsander Halawa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This paper is based on the author's concern over the increasingly rampant events of human dignity decline. More of people are less aware of the nobility of their dignity as Imago Dei. The purpose of this writing is to make each individual aware himself as an individual who is able to respect and fight for their own dignity and the others, while also stopping damaging their own dignity and the dignity of others. The method used is a literature review. The author collects, reads, and understands various relevant sources and compiles them into a scientific paper. The results of this research illustrate that humans have a very noble dignity based on their identity as Imago Dei. Humans are bestowed by God with various privileges, such as mind, consciousness, and free will. Therefore, God entrusts humans as His co-workers in the work of creation, and God even gives them the mandate to maintain and guard other creations. Based on their existence, humans live in a trilogy of relationships, namely relationships with God, others, and the universe. Because humans, by their nature, humans are social beings and are the pinnacle of all of God's creations, everyone must respect their own dignity and that of other humans. Humans should live in an atmosphere of universal brotherhood, tolerance, dialogue and peace with each other and the universe.